Sistem Pendukung Keputusan Berbasis AHP untuk Pemilihan Hunian di Kawasan Perkotaan yang Padat - Yessy Evita Leony Aruan; Nanda Novita (Sistem Pendukung Keputusan dengan Aplikasi, 2025)
Home selection is a critical and complex decision, particularly in densely populated urban areas such as Medan, where multiple factors including location, price, facilities, and environmental risks must be considered simultaneously. This study aims to develop a Decision Support System model based on the Analytical Hierarchy Process (AHP) to assist prospective buyers in making more objective and structured housing decisions. The research evaluated 20 housing alternatives selected through purposive sampling. Assessments of criteria and alternatives were conducted by five respondents, consisting of two property experts, two information systems academics, and one experienced homebuyer, using pairwise comparison questionnaires based on the Saaty scale. The analysis reveals that Location holds the highest weight (0.6333), followed by Income/Property Price (0.2605), and Facilities (0.1062). At the sub-criteria level, Flood-Free Area emerged as the most influential factor with a weight of 0.3533, followed by Property Price (0.1954) and Safe Neighborhood (0.1668). Among the 20 alternatives, Cempaka Lestari ranked first with a score of 0.9040, closely followed by Griya Indah (0.9033) and Anggrek Residence (0.8930). The consistency ratio for all calculations was below 0.10, confirming the reliability and logical validity of the judgments. These findings emphasize that location-specific environmental criteria, particularly flood risk, play a decisive role in homebuyer preferences in Medan. Practically, the proposed model provides prospective buyers with a rational decision-making framework and offers strategic insights for developers to align housing products with market demands in flood-prone urban areas.